Comparative Analysis of Profitability, Credit Risk and Operational Efficiency Between State-Owned Banks and National Private Banks on the IDX for the Period 2020-2024 - Dinda Nashra Aji Kurnia; F Fauziyah; Ahmad Yani (LP2M IAIN Palopo, 2026)
The financial performance of national commercial banks and State-Owned Enterprises (SOEs) listed on the Indonesia Stock Exchange between 2020 and 2024 will be examined and contrasted in this study. Three main criteria are used to assess financial performance: operational efficiency, credit risk, and profitability. Return on Equity (ROE), Return on Assets (ROA), and Net Interest Margin (NIM) are used to evaluate profitability. Non-performing loans (NPLs) serve as a stand-in for credit risk, and the operating expenses to operating income ratio (BOPO) is used to gauge operational effectiveness. The research uses secondary data from audited annual financial statements and takes a quantitative method with a comparative design. Eight banks make up the sample, including four state-owned and four national private banks, for a total of 40 observations. Descriptive statistics, the Shapiro-Wilk normality test, the independent sample t-test, and the Mann-Whitney U test were used to evaluate the data. The results show that, across all examined metrics, state-owned banks and national private banks do not significantly differ in terms of their financial performance. This finding implies that ownership structure is not the main factor influencing banking performance. The study has consequences for bank management and regulators in formulating strategic choices and regulations meant to preserve banking stability and enhance performance. It also lays the groundwork for further studies that will broaden the study by introducing other variables and methodological techniques.